The potential diagnostic power of CD138+ microparticles from the plasma analysis for multiple myeloma clinical monitoring. Issue 4 (9th September 2019) - Liu, Zhao‐Yun; Tian, Meng‐Yue; Deng, Ling; Wang, Ying‐Shuai; Xing, Rui; Liu, Hui; Fu, Rong
Abstract: Multiple myeloma (MM) is malignant tumor with abnormal proliferation of bone marrow plasma cells. The existing clinical tools used to determine treatment response and tumor relapse are limited in sensitivity. We investigated the CD138+ microparticles (MPs) of MM patients to find out whether MPs could provide a novel means to monitor the malignant cells in MM patients. Our study showed that the levels of MPs were significantly elevated in MM patients. The MP counts in peripheral blood from new diagnosed MM patients were significantly higher than patients in CR and HD. Consist with the total MPs, the number of the PC‐derived MPs (CD138+) increased in BM from MM patients compared with CR and HD. The ratio of the PC‐derived MPs (CD138+) in BM increased in MM patients compared with CR and HD. The correlation test revealed that the CD138+ MPs in BM and PB were all positively correlated with the plasmacyte ratio in bone marrow (BMPC) and the β2 ‐MG. New diagnosed MM patients and controls were compared, and ROC curves were used to identify cutoff points with optimal sensitivity and specificity concerning the ratios and counts of CD138+ MPs in BM and PB. The AUC of the CD138+ MP counts in BM was 0.767, and in PB was 0.680. The AUC of the CD138+ MP ratios in BM was 0.714, and in PB was 0.666. According to this, the counts of CD138+ MPs in BM showed to be a powerful marker of diagnosis. We demonstrated that CD138+ MPs from the plasma provide support for a potential monitoring biomarker of MM.